Global Perspectives of Nanoscience and Engineering Education - Winkelmann, Kurt; Bhushan, Bharat (Science Policy Reports, 2016)
This book presents the perspectives of nanotechnology educators from around the world. Experts present the pressing challenges of teaching nanoscience and engineering to students in all levels of education, postsecondary and informal environments. The book was inspired by the 2014 NSF workshop for Nanoscience and Engineering Education. Since nanotechnology is a relatively new field, authors present recommendations for designing nanotechnology education programs. The chapters describe methods to teach specific topics, such as probe microscopy, size and scale, and nanomaterial safety, in classrooms around the world. Other chapters describe the ways that organizations like NNIN and the NISE Network have influenced informal nanotechnology education. Information technology plays a growing role in all types of education and several chapters are devoted to describing ways how educators can use online curricula for teaching nanotechnology to students from preschool to graduate school.